2021
DOI: 10.1590/1678-4499.20200447
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of sweet potato in response to the application of nitrogen rates and paclobutrazol

Abstract: The excess of nitrogen (N) causes the overgrowth of sweet potato foliage, increasing the self-shading and reducing the root yield. Therefore, a combined N and paclobutrazol (PBZ) application can reduce the vegetative overgrowth and benefit the sweet potato yield. The purpose of this study was to evaluate the plant growth, yield, uptake and removal of N by sweet potato plants fertilized with N and treated with PBZ during two planting seasons. The treatments consisted of four N rates (0, 50, 100 and 200 kg•ha -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Abdallah et al [12] evaluated the performance of sweet potato clones under different watering strategies in the coastal lowlands of Kenya. Ribeiro et al [13] conducted a study to evaluate the plant growth, yield, uptake, and removal of N by sweet potato plants fertilized with N and treated with paclobutrazol during two planting seasons. Pepó [14] showed that a 0.75 m row spacing was more favourable than a 1.0 m one in Hungary.…”
Section: Introductionmentioning
confidence: 99%
“…Abdallah et al [12] evaluated the performance of sweet potato clones under different watering strategies in the coastal lowlands of Kenya. Ribeiro et al [13] conducted a study to evaluate the plant growth, yield, uptake, and removal of N by sweet potato plants fertilized with N and treated with paclobutrazol during two planting seasons. Pepó [14] showed that a 0.75 m row spacing was more favourable than a 1.0 m one in Hungary.…”
Section: Introductionmentioning
confidence: 99%